GENOTYPE BY ENVIRONMENT INTERACTION AND ASSOCIATION OF MORPHO-YIELD VARIABLES IN UPLAND COTTON - S. Gul; N. U. Khan; S. Batool; M. J. Baloch; M. Munir; M. Sajid; A. A. Khakwani; S. H. Ghaloo; Z. A. Soomro; S. F. Kazmi (Journal of Animal and Plant Sciences, 2014)
Legacy of seed cotton yield and other quantitative traits is highly persuaded by environmental aspects, therefore, phenotypic response of a genotype is ascertained by genetic and environmental factors upon it, although occurrence of a third effect, of no less importance i.e. genotype-by-environment interaction (GEI). Studies were conducted in 2010 and 2011 evaluating G × E interactions and correlation in upland cotton using randomized complete block design at the University of Agriculture, Peshawar, Pakistan. The GEI was characterized using eight upland cotton cultivars viz., SLH-284, CIM-446, CIM-473, CIM-496, CIM-499, CIM-506, CIM-544 and CIM-707. Significant (p≤0.01) mean squares for genotypes, environments and G × E interactions revealed genetic variability among cotton genotypes as well as environments inconsistency. The contribution to the total sums of squares, regardless of trait, revealed that genotypes and genotype × environment play principal role followed by environments, while replications (experimental error) share was minimal. The environment accounts for 61.86%, 26.99% and 18.64% of total variation for bolls plant-1, seed cotton yield and sympodia plant-1, respectively, considering the larger effects of environment in combination with genotypes on plant growth and morphology. Seed cotton yield has significant (p≤0.01) positive correlation with boll number, and positive with morphological traits. Based on two-year studies, CIM-496 exhibited the best performance followed by CIM-554 and SLH-284 for improvement in seed cotton and lint yields.
Keywords: G × E interactions; total sum of squares; traits association; seed cotton yield; Gossypium hirsutum L